2021
DOI: 10.1038/s41380-021-01093-2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and behavioral divergence of ketamine enantiomers: implications for abuse liability

Abstract: Ketamine, a racemic mixture of (S)-ketamine and (R)-ketamine enantiomers, has been used as an anesthetic, analgesic and more recently, as an antidepressant. However, ketamine has known abuse liability (the tendency of a drug to be used in non-medical situations due to its psychoactive effects), which raises concerns for its therapeutic use. (S)-ketamine was recently approved by the United States’ FDA for treatment-resistant depression. Recent studies showed that (R)-ketamine has greater efficacy than (S)-ketam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
116
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(137 citation statements)
references
References 82 publications
(115 reference statements)
7
116
1
Order By: Relevance
“…Whether this is the result of a direct or indirect interaction of ketamine remains unclear. The degree of ketamine’s interaction with these varied targets is concentration dependent, making the consideration of dosage critical in experimental design ( Bonaventura et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whether this is the result of a direct or indirect interaction of ketamine remains unclear. The degree of ketamine’s interaction with these varied targets is concentration dependent, making the consideration of dosage critical in experimental design ( Bonaventura et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have demonstrated a significant escalation of intravenous (es)ketamine intake during repeated self-administration sessions in rats. 26 , 27 However, tolerance to daily oral ketamine treatment in patients with chronic pain is not often observed. 11 , 28 This may be because the oral route of administration is associated with a lower risk of misuse in general, 12 and that after oral intake, the main metabolite norketamine reaches higher plasma levels as a result of extensive first-pass metabolism, and might have a more favourable safety profile than ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…This is counterbalanced by evidence that (S)-norketamine, the metabolite of (S)-ketamine, was found to have greater antidepressant efficacy in rodents than its complement, (R)-norketamine, when tested in inflammation-induced and chronic social defeat stress models ( 64 ). Another argument for (R)-ketamine is evidence of lower levels of abuse risk in rodent models based on tests of self-administration, conditioned place preference, induced locomotor activity, induced psychomotor sensitization, and impact on metabolic activity and dopamine tone in the mPFC, as compared with (R,S)-ketamine or (S)-ketamine ( 65 ). Despite these results from rodent research, and its use as a recreational substance, ketamine is not considered a highly addictive drug ( 11 , 12 , 15 , 17 ).…”
Section: Therapeutic Effects Of Ketaminementioning
confidence: 99%
“…The most prominent risk for a state-altering substance such as ketamine is its abuse liability—the drug's potential for misuse outside of the therapeutic environment due to its psychoactive effect. Racemic ketamine has some demonstrated abuse liability in both animal and human studies, though there appear to be important differences between R and S enantiomers of ketamine: rats self-administered (S)-ketamine, but not (R)-ketamine, in subanesthetic doses; (S)-ketamine, but not (R)-ketamine, induced locomotor activity described as similar to opioid receptor-dependent behavior; (S)-ketamine also induced psychomotor sensation and conditioned place preference in mice, and selectively increased metabolic activity and dopamine tone in medial prefrontal cortex of rats ( 65 ).…”
Section: Therapeutic Effects Of Ketaminementioning
confidence: 99%